Neuromarketing: Building Brands through Neuroscience - Ch Siddharth Nanda, Dr. Ankita Chakravarty Bhattacharya (International Journal of Modern Agriculture, 2021)
Neuromarketing is an extension of Neuroscience and Marketing. It studies the brain responses to advertising messages, appeals, and images that influences the consumer behaviour. The responses of consumers to various marketing campaigns are measured using various tools of neuromarketing. This paper includes the meaning of Neuromarketing, its tools, and examples of Neuromarketing by organizations